RANTAI NILAI (Value chain) PRODUK JAHE (Zingiber officinale) DI KAMPUNG WARSANSAN, DISTRIK BIAK UTARA, KABUPATEN BIAK NUMFOR, PROVINSI PAPUA - Widati, Agatha W.; Erubun, Christina Martha; Simanungkalit, Saut M. P. (Department of Social Economic Agriculture, Faculty of Agriculture, University of Papua, Manokwari, West Papua, Indonesia, 2024)
The people of Warsansan Village who work at KTH Nyampun Kampung Warsansan earn income from the sale of Ginger and Ginger Juice. Based on this, this study focuses on the Value Chain, Supply Chain and Added Value of Ginger Products. Sampling was purporsive sampling, accidental sampling, and snowball sampling. The value chain activities of ginger products in Warsansan Village, North Biak District, Biak Numfor Regency are: Ginger farmers provide ginger raw materials on the land, Ginger juice processors do not buy raw materials and do not store them in the warehouse but directly process them, Ginger juice processors take raw materials on their own land so that there is no price for raw materials, The process of processing ginger plants into ginger juice products in Warsansan Village is still using a very simple way most of the time processing ginger juice products in residential houses, because there is no production house yet. The marketing of the product is carried out directly and the delivery outside the city and the shipping cost is borne by the recipient of the goods. The supply chain flow in this study is